Long-Term Survey Is Necessary to Reveal Various Shifts of Microbial Composition in Corals - Yang, Shan-Hua; Tseng, Ching-Hung; Huang, Chang-Rung; Chen, Chung-Pin; Tandon, Kshitij; Lee, Sonny T. M.; Chiang, Pei-Wen; Shiu, Jia-Ho; Chen, Chaolun A.; Tang, Sen-Lin (Frontiers in Microbiology, 2017)
The coral holobiont is the assemblage of coral host and its microbial symbionts, which functions as a unit and is responsive to host species and environmental factors. Although monitoring surveys have been done to determine bacteria associated with coral, none have persisted for >1 y. Therefore, potential variations in minor or dominant community members that occur over extended intervals have not been characterized. In this study, 16S rRNA amplicon pyrosequencing was used to investigate the relationship between bacterial communities in healthy Stylophora pistillata in tropical and subtropical Taiwan over 2 y, apparently one of the longest surveys of coral-associated microbes. Dominant bacterial genera in S. pistillata had disparate changes in different geographical setups, whereas the constitution of minor bacteria fluctuated in abundance over time. We concluded that dominant bacteria (Acinetobacter, Propionibacterium, and Pseudomonas) were stable in composition, regardless of seasonal and geographical variations, whereas Endozoicomonas had a geographical preference. In addition, by combining current data with previous studies, we concluded that a minor bacteria symbiont, Ralstonia, was a keystone species in coral. Finally, we concluded that long-term surveys for coral microbial communities were necessary to detect compositional shifts, especially for minor bacterial members in corals.